Bilateral Ewing Sarcoma/Primitive Neuroectodermal Tumor of the Breast: A Very Rare Entity and Review of the Literature. (30th May 2013) - Majid, N.; Amrani, M.; Ghissassi, I.; El Cadi, M.; El Bouzidi, M.; El Kabous, M.; Kherbach, A.; Errihani, H.
Abstract : Peripheral primitive neuroectodermal tumors (PNET) are rare malignant tumors, affecting mostly children and adolescents and have been described in breast in eight case reports only. In this paper, we present a case of bilateral mammary ES/PNET where distinction between primary and metastatic diseases was discussed through a literature review. The aim of this work is to demonstrate that although rare, the possibility of PNET should be kept in mind while evaluating a palpable breast abnormality in a young female.